THE ANALYSIS OF STUDENTS' LEARNING DIFFICULTIES IN MATHEMATICS ALGEBRAIC ARITHMETIC OPERATION - Sumardin Raupu; Nurdin K; Hasriana; Afrisal Said (JF Publisher, 2023)
Math is a difficult and complicated subject to apply and understand for some students. This learning difficulties has an impact on their learning achievement. Therefore, this research aims to determine the learning difficulties of algebraic arithmetic operations in high score group students, moderate score group students and low score group students at SMPN 5 Palopo. This research is descriptive quantitative research which aims to examine an objective picture through the numbers. The population in this research is all students of class VIII C at SMPN 5 Palopo, consist of 25 students. The sample was conducted by saturated sampling that the entire population will be sampled when it is less than 30 people. The data in this research were analyzed using the percentage formula for the level of students’ difficulty. The results indicated that students with high score groups did not experience concept and principal difficulties, but the students experienced verbal difficulties of 33% with a very low category. Meanwhile, the students with moderate score groups experienced concept difficulties of 11% with a very low category, principal difficulties of 6% with a very low category, and verbal difficulties learners of 46% with a moderate category. In addition, the students with low score groups experienced concept difficulties of 61% with a high category, principal aspect difficulties of 60% with a medium category, and verbal difficulties of 59% with a medium category.